Prinsip Belajar Mengajar dalam Analekta yang Terkandung pada Film Kungfu Panda dan Kungfu Panda 2 - Agustinus Sufianto; Patricia Patricia (Bina Nusantara University, 2013)
The Analects is one of the famous books from China which records Confucius’ teachings. Kungfu Panda and Kungfu Panda 2 are two famous animation films from America. After seeing these movies, there are some similar values that can be found between the movies and The Analects, especially in education field. The writer limited the scope into teaching and learning principles. The writer defined 2 main issues. First is to explain the correlation between Kungfu Panda and Kungfu Panda’s teaching and learning principles with The Analects. Second is to understand those principles and its application in our daily lives. This research method is library research. The results stated that there are some correlation between Kungfu Panda, Kungfu Panda 2, and The Analects. Analyzing the correlation will help us to understand more about Confucius’ teaching, especially in education field.